What inflation disrupts? A comment on "Inflation - Pragmatics of money and inflationary sensoria"by Federico Neiburg - Jeanne Lazarus (economic sociology. perspectives and conversations, 2023)
Talking about money means talking about practices, morals, policies, the banking system, the social system, families, inequalities, poverty, wealth, measure, excess, or lack. However, most often, money is approached as a fixed point around which individuals, societies, banks, or policies move. Inflation jeopardizes this fixity in several ways: the value of saved money decreases or even collapses when the value of goods and services rises.
Keywords: 300